Evaluating the Influence of Substrate Types and Concentrations on Power Generation in Microbial Fuel Cells - Carlos Lopez, Midon; Nor Azalina, Rosli; Inawati, Othman; Sandy Belening, Stephen (2025)
Microbial fuel cells (MFCs) offer a sustainable solution for simultaneous wastewater treatment and electricity generation. This study investigates the impact of different substrate types glucose (1 g/L, 3 g/L, 5 g/L), sago wastewater, and landfill leachate on MFC performance. A dual-chamber MFC system with stainless steel electrodes and salt bridge was used over a 5-day batch operation. Voltage output and Chemical Oxygen Demand (COD) removal efficiency were recorded. The highest COD removal (56%) was achieved with 1 g/L glucose, while the highest voltage output (392 mV) came from 3 g/L glucose. Landfill leachate also performed well, showing 50% COD removal and 382 mV peak voltage. Sago wastewater showed moderate performance. These results underscore the importance of substrate selection and concentration in optimizing MFC systems for renewable energy and wastewater treatment.